Minimal important difference for 6-minute walk test distances among patients with chronic heart failure - Täger, Tobias; Kowall, Wiebke; Cebola, Rita; Fröhlich, Hanna; Franke, Jennifer; Dösch, Andreas; Katus, Hugo; Wians, Frank H.; Frankenstein, Lutz (International journal of cardiology, 2014)
Background - The 6-minute walk test (6WT) is an established tool in the assessment of endurance and prognosis in patients with chronic heart failure (CHF). For these patients there is very limited data on biological variation of 6WT distances. We determined the minimal important difference (MID) for the 6WT in patients with stable systolic CHF. - Methods - Two cohorts of patients with stable systolic CHF were included from the outpatients' clinic of the University of Heidelberg. In these cohorts, two 6WT measurements were performed - in cohort 1 (n=461) 180days and in cohort 2 (n=512) 365days apart. Stability was defined as the absence of clinical events (3months before the first test, between both tests, and 6months after the second test) and stability of symptoms (NYHA) between tests. Using a standard error of measurement (SEM)-based approach, we determined the MID for both cohorts. - Results - The intraclass correlation coefficient was 0.89 at 180days and 0.88 at 365days. The results were consistent for groups stratified for age, gender, etiology of CHF, and individual NYHA class. The MID for the 6WT in stable CHF patients was 35m and 37m between presentation and 180 and 365days, respectively. - Conclusion - Submaximal exercise capacity as represented by the 6WT varies little in stable CHF patients for up to 1-year intervals. The MID for changes in 6WT values in patients with stable CHF over a period of 6 to 12months is ~36m.